APPLICATION OF PROBLEM BASED LEARNING (PBL) MODEL BY MICROSOFT POWER POINT MEDIA TO IMPROVE ACTIVITIES AND RESULTS OF LEARNING SOCIAL SCIENCE OF SMP in MADIUN - Fatchur Rahman; Nurhadji Nugraha; Sudarmiani Sudarmiani (Social Sciences, Humanities and Education Journal (SHE Journal), 2020)
This study aims to determine the application of Problem Based Learning aided by Microsoft PowerPoint in improving social studies learning outcomes for SMP Negeri 2 Madiun. This class action research uses the Kemmis and Mc Taggart model, which includes planning, action, observation, and reflection. This research uses qualitative and quantitative analysis techniques. Data analysis techniques used in this study focus on three assessments, namely the assessment of the cognitive, affective, and psychomotor domains. This study was carried out in the even semester of 2019/2020 school year. The minimum completeness criteria for social studies subjects in the 2013 curriculum for 8th grade students is 75. The study concludes that the Problem Based Learning (PBL) Model assisted by Microsoft PowerPoint can improve the learning outcomes of Social Studies in 8th grade of SMP Negeri 2 Madiun